End game [compact disc, unabridged] - Baldacci, David (Baldacci, David. Will Robie series., 2017)
Will Robie returns home from a mission overseas to discover that his boss--code named Blue Man--has vanished. His last known location was in remote Colorado, and there have been no other sightings or communications since. But there is violence brewing in this small town, and Robie and his sometime partner Jessica Reel will be lucky if they make it out alive--with or without Blue Man.